PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (CAPSICUM FRUTESCENT L.) KULTIVAR DEWATA PADA PERLAKUAN BERBAGAI JENIS PUPUK KANDANG DAN UMUR BIBIT - Jumadi, Jumadi; Budirokhman, Dodi; Nur, Subandi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2024)
This study aims to determine the influense of the type of manure and the age of seedlings on the growth and yield of cayenne pepper plants (Capsicum frutescent L). This research was conducted in Bayalangu Kidul Village, Subdistricts of Gegesik, District of Cirebon – West Java, from March until Juny 2018. The Method used to experimental method using a Rendomized Blok Design patterns, treatment consists of two factors were repeted three times. The first factor is a type of manure consists of chicken manure, goat manure and cow manure. While the second factor is age of seed consists of age of seed 20, 30 and 40 days after seedling. The results of the study showed the real difference between types of manure and age of seedlings against plant height, number of leaves, number of fruit cropping and planting as well as fruit weight cropping and planting. On the treatment A (chicken manure and 20 days after seedling), B (chicken manure and 30 days after seedling), C (chicken manure and 40 days after seedling), E (goat manure and 30 days after seedling) and F (goat manure and 40 days after seedling) increase the weight of the fruit.